2011
DOI: 10.1519/jsc.0b013e318212e3ce
|View full text |Cite
|
Sign up to set email alerts
|

Electromyostimulation—A Systematic Review of the Influence of Training Regimens and Stimulation Parameters on Effectiveness in Electromyostimulation Training of Selected Strength Parameters

Abstract: Our first review from our 2-part series investigated the effects of percutaneous electromyostimulation (EMS) on maximal strength, speed strength, jumping and sprinting ability, and power, revealing the effectiveness of different EMS methods for the enhancement of strength parameters. On the basis of these results, this second study systematically reviews training regimens and stimulation parameters to determine their influence on the effectiveness of strength training with EMS. Out of about 200 studies, 89 tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 48 publications
(235 reference statements)
4
102
1
2
Order By: Relevance
“…We are unaware of any study that has compared the strengthening effects of different types of NMES that produced different torques during training. The work that has been done in this area typically examines strength gains from NMES in comparison to control groups or other non-NMES interventions (Filipovic, Kleinöder, Dörmann, and Mester, 2011;Maddocks, Gao, Higginson, and Wilcock, 2013;Stevens, Mizner, and Snyder-Mackler, 2004). We do know that in general there is a positive correlation between the percentages of MVIC produced during training and subsequent strength gains (Filipovic, Kleinöder, Dörmann, and Mester, 2011;Selkowitz, 1989;Snyder-Mackler, Delitto, Stralka, and Bailey, 1994;Stevens-Lapsley et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are unaware of any study that has compared the strengthening effects of different types of NMES that produced different torques during training. The work that has been done in this area typically examines strength gains from NMES in comparison to control groups or other non-NMES interventions (Filipovic, Kleinöder, Dörmann, and Mester, 2011;Maddocks, Gao, Higginson, and Wilcock, 2013;Stevens, Mizner, and Snyder-Mackler, 2004). We do know that in general there is a positive correlation between the percentages of MVIC produced during training and subsequent strength gains (Filipovic, Kleinöder, Dörmann, and Mester, 2011;Selkowitz, 1989;Snyder-Mackler, Delitto, Stralka, and Bailey, 1994;Stevens-Lapsley et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…An additional potential mechanism of NMES-induced strength gains is improvement in volitional muscle activation (Maffiuletti, 2010). Regardless, strength gains from NMES are proportional to the forces produced during training with higher training forces resulting in greater strength gains (Filipovic, Kleinöder, Dörmann, and Mester, 2011;Selkowitz, 1985;Snyder-Mackler, Delitto, Stralka, and Bailey, 1994;Stevens-Lapsley et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…However, the muscle loading need at least 50% MVC force to induce muscle hypertrophy for the healthy subjects [24]. In contrast, muscle loading induced electrical stimulation could also be enhanced by increasing electrical current intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have suggested that it was necessary to induce muscle strengthening at least 50% MVC [24] [25]. In addition, the pain was depended on current intensity [26].…”
Section: Training Protocol With Electrical Stimulation With Eccentricmentioning
confidence: 99%
“…The carrier frequency was set at 4 kHz. The pulse duration was fixed at 125 μs to induce sufficient muscle activation [29]. The current intensity was set within the range of the minimum visible contraction of the calf muscles.…”
Section: Neuromuscular Electrical Stimulation Groupmentioning
confidence: 99%